2022
DOI: 10.3389/fcvm.2021.787740
|View full text |Cite
|
Sign up to set email alerts
|

ACEI/ARB Medication During ICU Stay Decrease All-Cause In-hospital Mortality in Critically Ill Patients With Hypertension: A Retrospective Cohort Study Based on Machine Learning

Abstract: Background: Hypertension is a rather common comorbidity among critically ill patients and hospital mortality might be higher among critically ill patients with hypertension (SBP ≥ 140 mmHg and/or DBP ≥ 90 mmHg). This study aimed to explore the association between ACEI/ARB medication during ICU stay and all-cause in-hospital mortality in these patients.Methods: A retrospective cohort study was conducted based on data from Medical Information Mart for Intensive Care IV (MIMIC-IV) database, which consisted of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Otaguro et al evaluated data from patients who underwent intubation for respiratory failure and received mechanical ventilation in ICU and use three learning algorithms (Random Forest, XGBoost, and LightGBM) to predict successful extubation, the result demonstrated that lightGBM exhibited the best overall performance [ 30 ]. Moreover, Yang et al adopted nine machine learning models to predict in-hospital mortality in critically ill patients with hypertension and found that among nine machine learning models, the lightGBM model had the best predictive ability [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Otaguro et al evaluated data from patients who underwent intubation for respiratory failure and received mechanical ventilation in ICU and use three learning algorithms (Random Forest, XGBoost, and LightGBM) to predict successful extubation, the result demonstrated that lightGBM exhibited the best overall performance [ 30 ]. Moreover, Yang et al adopted nine machine learning models to predict in-hospital mortality in critically ill patients with hypertension and found that among nine machine learning models, the lightGBM model had the best predictive ability [ 31 ].…”
Section: Discussionmentioning
confidence: 99%